A Review of Resonant Converter Control Techniques and The Performances - Tarmizi, Ahmad Izzuddin; Jali, Mohd Hafiz; Hafez , Sarkawi (2013)
paper first discusses each control technique and then gives experimental results and/or performance to highlights their merits. The resonant converter used as a case study is not specified to just single topology instead it used few topologies such as series-parallel resonant converter (SPRC), LCC resonant converter and parallel resonant converter (PRC). On the other hand, the control techniques presented in this paper are self-sustained phase shift modulation (SSPSM) control, self-oscillating power factor control, magnetic control and the H-∞ robust control technique.